Application of Plastic Ball Modification through Teams Games Tournament Learning Model to Improve Volleyball Lower Passing in Class V MI Ath-Thohariyah - Iqbal Gunawan; Ani Kurniawati (CV Media Inti Teknologi, 2024)
This study aims to determine the effect of applying modified plastic ball learning media on volleyball underhand passing at MI Ath-Thohariyah. Experimental research is the methodology employed in this study. employing a single kind of experimental study, namely the one group pretest-posttest pre-experimental design. The pupils in class V of MI Ath-Thohariyah will be the population employed in this study. A total of 25 male students from class V MI Ath-Thohariyah made up the sample for this study, which used non-probability sampling. The pre-test average was 49.36 after receiving a plastic ball modification therapy utilizing the Teams Games Tournament technique for 12 meetings, and the post-test score was 82.04, indicating that the rise was 32.68, according to the t test results. Furthermore, the t-count value is 23.43 according to the t-test. 1.71 is the t-table value at a significant level of 5% and a df of 24. It is therefore possible to state that there is a significant increase in the score of the lower passing ability results by being given a plastic ball modification using the teams games tournament method for 12 meetings because t-count > t-table (23.43 > 1.71) and the significance value is smaller than 0.05 (0.00 < 0.05).